Segmental arterial mediolysis with abdominal angina: case report - Teixeira, João Vilson Claudio (2021)
To report a rare case of a patient diagnosed with segmental arterial mediolysis with abdominal angina. The work is characterized as a Case Report with bibliographic review, the method used was the bibliometric analysis of articles published in the Pubmed database. The theoretical scan covered the years 2010 to 2020, and consisted of seeking out articles throughout all indexes using the terms: segmental arterial mediolysis and abdominal angina. The search occurred between the months of October and December of 2020. The information contained for the case report was obtained by the review of medical records, patient interview as well as records of laboratory tests and images. A 57-year-old man was diagnosed with segmental arterial mediolysis with abdominal angina after a series of investigations and imaging exams. These investigations were prompted due to a long- standing complaint of unexplained abdominal pain that had gone undiagnosed by other specialists. The evaluation of this pathology objectively requires the attainment of the earliest possible resolution, thus, cli entary investigations must be carried out. To date, however, there are no established guidelines on therapy.